Citizen's choice - Barker, Ernest (Cambridge, 1938)
The papers collected in this little volume, under a title for which I have to thank the insight and the ingenuity of the Secretary of the Cambridge University Press, belong to a most stirring period in the history of human affairs. They were all composed in the years from 1933 to 1937, between the beginning of the National Socialist Revolution in Germany and the end (not yet in sight) of the Civil War in Spain. In a world perplexed by the problem of choice I have sought to consider the great alternatives. In a country which still follows the great tradition inaugurated in the seventeenth century the tradition of Milton and Cromwell$1 (BI have tried to obey the teaching of my masters. I have remembered, even if I have not fulfilled, the noble injunction of Milton, 'to argue freely according to conscience'. I have remembered, even if I have sometimes failed to follow, the saying of Cromwell in Putney Church in the autumn of 1647: 'If we may come to an honest and single debate, in one common way for publicgood; if we meet so, we shall meet with great deal the more comfort and hopes of a good and happy issue and understanding of the business. But if otherwise, I despair.'s
Keywords: Political Science